Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3747/co.24.3554
|View full text |Cite
|
Sign up to set email alerts
|

Training Oncoplastic Breast Surgeons: The Canadian Fellowship Experience

Abstract: Background Oncoplastic breast surgery combines traditional oncologic breast conservation with plastic surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Variation in the management of DCIS has been demonstrated previously at both national and international levels including various ongoing studies regarding the optimal management of this disease [ 7 , 8 , 13 , 14 ]. A study looking at variation in practice in the UK, for example, demonstrated national differences in the rates of, and indications for, mastectomy, axillary management, and follow-up procedures for DCIS patients [ 15 , 16 , 17 ]. These international uncertainties regarding the optimal management of DCIS offer a possible explanation for the lack of consistency regarding its management across Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the management of DCIS has been demonstrated previously at both national and international levels including various ongoing studies regarding the optimal management of this disease [ 7 , 8 , 13 , 14 ]. A study looking at variation in practice in the UK, for example, demonstrated national differences in the rates of, and indications for, mastectomy, axillary management, and follow-up procedures for DCIS patients [ 15 , 16 , 17 ]. These international uncertainties regarding the optimal management of DCIS offer a possible explanation for the lack of consistency regarding its management across Canada.…”
Section: Discussionmentioning
confidence: 99%
“…The Society of Surgical Oncology offers 48 approved breast surgical oncology fellowship training programmes across the USA and Canada, but only 11 of these include some level of OBS training . In Canada, apart from the Society of Surgical Oncology fellowships, there are very few formal breast surgical oncology fellowships available . For example, the 1‐year programme offered through the University of Toronto accepts only one to two fellows per year and the curriculum contains no formal OBS training: the ability to independently perform OBS procedures is not one of the course's aims .…”
Section: Discussionmentioning
confidence: 99%
“…8 In Canada, apart from the Society of Surgical Oncology fellowships, there are very few formal breast surgical oncology fellowships available. 9 For example, the 1-year programme offered through the University of Toronto accepts only one to two fellows per year and the curriculum contains no formal OBS training: the ability to independently perform OBS procedures is not one of the Another major public hospital centre has developed its own integrated model, following a long-term collaboration between breast and plastic surgery … we have parallel lists and we have a clinic on the day when the all-day list is on so that breast surgeons come out of clinic and do the mastectomy and go back to clinic and plastic surgeons can actually start in clinic and then go to theatre, so the surgical team swaps. But it's just been persistence taking many years to work towards a model that we had defined many years prior and nothing happens quickly.…”
Section: Discussionmentioning
confidence: 99%
“…To realize the true potential of OBS in breast cancer management in Indian patients, there is an exigent need to create a well-trained work force of breast surgeons, radiologists, medical oncologists, radiation oncologists, geneticists, psychology counselors, and nurses who are aligned to the its ever-evolving principles and practices. Successful OBS training programs have been created in many countries [42,43]. To this effect, senior breast oncoplastic surgeons from India and the UK have created a structured training program from aspiring breast oncoplasty surgeons [www.breastoncoplasty.org].…”
Section: Need For Obs Training In Indiamentioning
confidence: 99%